Accountability and Transparency in The Management of Village Fund Allocation - Nur Afni Bungaeja; Haliah Haliah; Nirwana Nirwana (Return : Study of Management, Economic and Bussines, 2024)
This research aims to determine and assess the accountability and transparency of village fund proxy management carried out by the Bakaru Village Government of Pinrang Regency. This research is a descriptive qualitative research with data collection techniques, namely interviews. The results of this study show that the management of village fund allocation in Bakaru is in accordance with the applicable laws regulated in the Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management. The results of the Management Accountability research in Bakaru Village have been good, both technically and administratively as seen from the information on the management of village fund allocation that can be easily accessed and the implementation of programs that always involve the community. Transparency in the management of village fund allocation in Bakaru Village is also transparent, this can be seen from the existence of easily accessible information and good communication between village officials and the community so that management is considered transparent. Even though the management of village fund allocation in Bakaru Village can be categorized as good, training and coaching on village fund management needs to be intensified by village officials, especially those directly involved in managing village fund allocation to be more directed in accordance with applicable regulations so that accountability and transparency in village fund allocation management can be maintained.